Paleoenvironmental background of the Early Pleistocene Gigantopithecus fauna in Bubing Basin, south China. (1st April 2017) - Huang, Shengmin; Hong, Hanlie; Bae, Christopher J.; Cheng, Liuling; Li, Dawei; Liao, Wei; Yin, Ke; Wang, Chaowen; Wang, Wei
Abstract: Thanks to the presence of the enigmatic Gigantopithecus fossils, vertebrate paleontologists have spent much time analyzing the Pleistocene faunas of southern China. Although research has been conducted in the region for more than one half century, the vast majority of this research has focused on the direct analysis of the associated vertebrate fossils, particularly for taxonomic identification purposes. In order to develop a firmer understanding of the paleoenvironment in which these various taxa lived there is still a relative paucity of data derived from other lines of evidence besides taxonomic identifications. Here, we contribute to these paleoenvironmental reconstructions of southern China by presenting the results of clay mineral composition and geochemical analyses of the deposits from the Early Pleistocene Mohui Cave (Bubing Basin, Guangxi). In general, the Mohui Cave clay mineral samples are dominated by kaolinite, which indicates a warm and humid climate. The relatively high content of smectite in Unit II implies a relatively long dry season within the overall context of the warm and humid environment. Based on the Chemical Index of Alteration (CIA), the estimated land surface temperature during the Early Pleistocene (27 °C) was much higher than today (21.9 °C). Our results are consistent with previous environmental reconstructions based on vertebrate paleontological and isotopic studies of the Gigantopithecus fauna in southern China that the environment during the Early Pleistocene was warmer and more humid than today.